2022
DOI: 10.1148/radiol.211680
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Evaluation of Multiparametric MRI Clear Cell Likelihood Scores in Solid Indeterminate Small Renal Masses

Abstract: GENITOURINARY IMAGING R enal masses are commonly encountered as incidental findings in patients undergoing cross-sectional imaging (1,2). The majority of solid small (4 cm [cT1a]) renal masses (SRMs) are malignant, but up to 20% are benign (3,4). Moreover, even when malignant, cT1a renal cell carcinoma (RCC) is frequently indolent and, when treated, rarely recurs locally or metastasizes (5). Indeed, cT1a RCC is an uncommon cause of patient mortality, particularly in older patients who may have other competing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…The reported radiologists’ experience ranged from 1 to 30 years, with inter-reader agreement measured with kappa value of 0.53-0.65. Regarding cutoff values, 3 studies reported that the results were derived from the threshold of ccLS ≥4 ( 26 , 28 , 30 ), whereas the remaining 3 studies reported results from both ccLS ≥3 and ccLS≥4 ( 19 , 27 , 29 ). Concerning technique characteristics, nearly all studies reported that the images acquired from 1.5T or 3.0 T MRI; however, in one study the field strength was not reported ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reported radiologists’ experience ranged from 1 to 30 years, with inter-reader agreement measured with kappa value of 0.53-0.65. Regarding cutoff values, 3 studies reported that the results were derived from the threshold of ccLS ≥4 ( 26 , 28 , 30 ), whereas the remaining 3 studies reported results from both ccLS ≥3 and ccLS≥4 ( 19 , 27 , 29 ). Concerning technique characteristics, nearly all studies reported that the images acquired from 1.5T or 3.0 T MRI; however, in one study the field strength was not reported ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…Concerning technique characteristics, nearly all studies reported that the images acquired from 1.5T or 3.0 T MRI; however, in one study the field strength was not reported ( 28 ). As for MRI protocol, only 3 studies used all sequences of T1, T2, dynamic contrast-enhanced (DCE), and diffusion-weighted imaging (DWI) ( 27 , 29 , 30 ). Concerning the reference standard, surgical resection pathological results were used in 4 studies, in the remaining 2 studies the biopsy results also were used in case of pathological results were not available ( 26 , 27 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 and supplementary Tables S6 and S7 provide a detailed description of the MRI sequences used in each study. The following studies used ccLS to diagnoses clear cell RCC from other renal masses: Steinberg et al, 18,43 Canvasser et al, 43 and Schieda et al 47…”
Section: Study Characteristicsmentioning
confidence: 99%
“…FIGURE 5: sROC curve of the sensitivity and specificity for each clear cell likelihood score (ccLS). Steinberg et al,18 Canavsser et al,43 and Schieda et al47 used ccLS scores to diagnose ccRCC. Point estimates were calculated using the linear mixed effects model for modeling multiple threshold data, as described by Schneider et al[40][41][42] The figure was generated using R.…”
mentioning
confidence: 99%